1991
DOI: 10.1210/jcem-72-4-773
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin Stimulation Test: Effects of Basal Cortisol Level, Time of Day, and Suggested New Sensitive Low Dose Test*

Abstract: Adrenal response to iv administration of 1-24 ACTH (250 micrograms) was examined in normal volunteers under various conditions. The effect of basal cortisol levels was examined by performing the tests at 0800 h with and without pretreatment with dexamethasone. The effect of time of day was evaluated by performing the tests at 0800 h and at 1600 h, eliminating possible basal cortisol influence by pretreatment with dexamethasone. In the first set of tests, despite significantly different baseline levels, 30-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
308
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(333 citation statements)
references
References 18 publications
19
308
1
5
Order By: Relevance
“…injection of 1 mg (1 -24)-corticotropin (tetracosactrin, Synacthen, Novartis Pharma, Berne, Switzerland) was given. One vial of 250 mg tetracosactrin was diluted in sterile saline solution to a concentration of 1 mg/ml, filtered in plastic syringes, and stored at 4 8C as described elsewhere (5). The tests were carried out on the day before the operation (day 2 1), immediately after the operation on the intensive care unit (ICU) (day 0), on the next 2 days in the ICU (day 1 and day 2), and before discharge from the hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…injection of 1 mg (1 -24)-corticotropin (tetracosactrin, Synacthen, Novartis Pharma, Berne, Switzerland) was given. One vial of 250 mg tetracosactrin was diluted in sterile saline solution to a concentration of 1 mg/ml, filtered in plastic syringes, and stored at 4 8C as described elsewhere (5). The tests were carried out on the day before the operation (day 2 1), immediately after the operation on the intensive care unit (ICU) (day 0), on the next 2 days in the ICU (day 1 and day 2), and before discharge from the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…However, this test is labor intensive and contraindicated in some patients. The low-dose (1 mg) ACTH test has recently been introduced and proved to be sensitive in revealing partial adrenal insufficiency by providing physiological adrenocortical stimulation (5,6). The results of the low-dose (1 mg) ACTH test correlate closely with those of the reference test for the function of the HPA axis (7), and are superior to the standard (250 mg) ACTH test (8).…”
Section: Introductionmentioning
confidence: 99%
“…The 250 mg dose is grossly supraphysiological and may induce false positive cortisol responses in some patients. The use of 1 mg ACTH and measurement of the 30-min cortisol value is a more sensitive test of adrenal function and identified a small subgroup of patients on long-term steroids, who responded normally to the regular 250-mg test, but had a reduced response to 1 mg [65]. It has been suggested that the 1-mg ACTH test follows the ITT more closely and may be more sensitive than the standard SST in detecting subtle deficiencies in the hypothalamic-pituitary-adrenal axis [66].…”
Section: The Short Synacthen Test (Sst)mentioning
confidence: 99%
“…injection of 250 mg corticotropin 1-24, the peak plasma corticotropin level is about 60 000 pg/ ml!! Dickstein et al (16), Broide et al (17) and Tordjman et al (18) recently published data on low-dose SCT tests (1 mg in adults or 0.5 mg/1.73 m 2 in children) that seemed to show that these low-dose SCTs are as sensitive as the IHT in detecting mild SAI in asthmatics who use topically applied corticosteroids or in patients with pituitary disease, although even a low-dose test can only measure adrenal reactivity but not endogenous ACTH reserve. Dickstein et al (16) maintained that with the low-dose test, the cortisol response at 30 min after i.v.…”
Section: The Low-dose Corticotropin Testmentioning
confidence: 99%